Industry and competitor analysis of the Norwegian marine insurance market - Ström, Johan (My University, 2012)
This thesis analyzes the Norwegian marine insurance market by identifying the threats and possibilities for an insurance company to expand on the Norwegian market. The thesis uses a constructive research method. The main focus is on a market analysis consisting of a specific competitor analysis. By knowing the competition, the scope of the market and the average profitability the thesis will give a direction for insurance company X on how to continue their expansion on the Norwegian market. This is done by identifying the competitors on the market and analyzing them one by one. In addition theme interviews with marine insurance brokers and a member of the Nordic marine insurance organization are held where the industry in general is analyzed. The analysis shows that the Norwegian market in general is stable and experiencing slow growth. This means that the competition is a market share competition. The hull insurance market is dominated by a few large insurers while the protection and indemnity is dominated by one insurer. If an insurer wants to expand on the Norwegian market it is important to choose the right partners, carefully evaluate every risk and expand slowly.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport